2019
DOI: 10.1007/s11274-019-2660-7
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS analysis of volatile organic compounds from Bambara groundnut rhizobacteria and their antibacterial properties

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…It is interesting to note that banana plant metabolome profile [2] Acidithiobacillus ferrooxidans also changed when subjected to pH stress [6] suggesting that membrane permeability was compromised under extreme acidity (pH 1.5). It was also found that Dunaliella salina cultivated under high NaCl stress (1.5M) demonstrated the increase of 9,12,15octadecatrienoic acid (Z,Z,Z) (C18:3 Δ9, 12,15 ) synthesis [7]. Similarly, in Chlamydomonas reinhardtii the synthesis of octadecatrienoic acid (C18:3) dan octadecadienoic acid (C18:2) also increased under NaCl stress [8].…”
Section: Introductionmentioning
confidence: 85%
“…It is interesting to note that banana plant metabolome profile [2] Acidithiobacillus ferrooxidans also changed when subjected to pH stress [6] suggesting that membrane permeability was compromised under extreme acidity (pH 1.5). It was also found that Dunaliella salina cultivated under high NaCl stress (1.5M) demonstrated the increase of 9,12,15octadecatrienoic acid (Z,Z,Z) (C18:3 Δ9, 12,15 ) synthesis [7]. Similarly, in Chlamydomonas reinhardtii the synthesis of octadecatrienoic acid (C18:3) dan octadecadienoic acid (C18:2) also increased under NaCl stress [8].…”
Section: Introductionmentioning
confidence: 85%
“…In addition, Palmitin, 1,2-di-, 2aminoethyl hydrogen phosphate was reported for its ability to interact with and enhances the antimicrobial activities of cationic surfactants (Joondan, et al, 2014). Other phytocompounds of the plant include 15-methyl Hexadecanoic acid methyl ester (7.71%) which has both antibacterial and antifungal activity (Chandrasekaran et al, 2011), 2,2-Dimethyl hexan-3-one (3.19%) which is an important volatile organic compound that has been isolated as part of major antimicrobially active compound responsible for the broad spectrum antimicrobial activity of the chloroform crude extract of the medicinal plant Datura metel (Hossain et al, 2013) and butanol extract of 3 Bacillus spp (Bacillus amyloliquefaciens, Bacillus thuringiensis and Bacillus sp), isolated from rhizoides of Bamfara nut, with strong antagonism against B. cereus, E. feacalis and Fusarium graminearium, all of which are known to cause infections in humans, animals and plants with high rates of mortalities (Ajilogba et al, 2019 However, despite its antimicrobial activity, it has been classified by the European Chemicals Agency (ECHA, 2017) as a potential human toxin that can cause eye, skin and gastrointestinal irritations. Its presence in Aloe vera stem therefore support the antimicrobial activity of the stem and potential health risks to humans.…”
Section: Discussionmentioning
confidence: 99%
“…A condition for GC analyses is that the analytes must be volatile enough to be able to be separated and detected. For this reason, many of the GC applications have been based on the characterization of the volatile compounds fractions of different plant or food matrices [ 23 , 24 , 25 ]. However, several non-volatile compounds can be derivatized prior to analysis in order to increase its volatility.…”
Section: Phytochemical Characterization Of Bioactive Compoundsmentioning
confidence: 99%